QoE‐ and energy‐efficient resource optimization in OFDMA networks with bidirectional relaying. Issue 13 (26th November 2015) - Ma, Xiaolin; Li, Fangmin; Ilow, Jacek; Chen, Zhizhang
Abstract: Because of the surging demands of multimedia services, quality‐of‐experience (QoE) is becoming an important metric to evaluate network quality from users' perspective. In this paper, resource optimisation to achieve optimal tradeoff between QoE and energy consumption in bidirectional orthogonal frequency‐division multiple‐access relaying networks is addressed so as to provide satisfactory multimedia delivery quality and support green communications. We first formulate a QoE‐energy efficiency tradeoff optimisation where QoE requirements and relaying traffic balance are considered and prove that QoE‐energy efficiency is quasiconcave on QoE, which suggests the existence of a unique global optimal tradeoff point. We then propose an optimisation framework to achieve the optimal tradeoff efficiently. With the framework, we develop resource allocation approaches for two specific relaying strategies, that is, two‐phase decode‐and‐forward relaying with dynamic XOR network coding and compute‐and‐forward relaying with physical network coding via structured codes. Numerical results validate theoretical findings and demonstrate the effectiveness of the proposed optimisation solution for achieving the tradeoff between QoE and energy consumption. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The resource optimization considering QoE and energy efficiency (QEE) tradeoff in bidirectional OFDMA relaying networks with dynamic network coding is investigated. Such QEE is proved to be quasi‐concave on QoE, making the formulated QEE optimization problem being a quasi‐concave optimization, which can be transformed into a sequence of feasibility problems that are governed by a bisection method. An efficient resource allocation strategy is then developed to obtain the optimal QEE point, and simulations validate its performance and the theoretical findings.